GAGASAN DAN PEMIKIRAN ZAKIYAH DARADJAT DALAM PENDIDIKAN ISLAM - Anita Indria (Program Pascasarjana UMSB, 2019)
Zakiyah Daradjat is an Islamic education figure with a background in psychology or religious psychology. She has her own views on Islamic education in providing education to students. Her ideas and thoughts give birth to the nature of education, in fact, do not see only one side, but see things more broadly. Based on the Qur'an, Sunnah, and ijtihad, Zakiyah revealed that education must always be associated with Islamic teachings and human needs so that the dynamics of Islamic education will continue to fly and in line with the challenges of the times. The basic aim of Islamic education is to nurture people to become pious servants of God with all aspects of their lives, deeds, thoughts and feelings. To achieve these objectives must involve the educational environment that is the responsibility in Islamic education. As for those responsible for Islamic education are parents, teachers, and the community where the process of running it requires educational tools as tools to help achieve the objectives of Islamic education.